Stank in de stad: Een onderzoek naar illegale lozingen in laatachttiende-eeuws Amsterdam - Raat, Sterre (Skript Historisch Tijdschrift, 2025)
The illegal disposal of sewage waste was a common problem in eighteenth-century Amsterdam and testimonies of these violations are found abundantly in the city’s archives. This article aims to contribute to the ‘healthscaping’ approach by analysing these testimonies. The method of healthscaping looks at different ways in which public health was regulated, in order to draw conclusions on premodern and non-Western public health. Based on ten testimonies of illegal disposals, it was found that both government and residents undertook action to limit illegal disposals, indicating they were concerned about the urban environment. In Amsterdam, so-called nightworkers were officially appointed for cleaning out cesspits. From the testimonies, it was noted that nightworkers were often involved in the fining of the (suspected) offenders. They had thus more responsibilities in public health regulation than previously known.